Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

High-speed imaging and proper orthogonal decomposition analysis of cavitation cloud evolution and interfacial instability in an artificially submerged coaxial jet - Yongfei Yang; Zijun Zhang; Weidong Shi; Xianglong Wu; Linwei Tan; Yupeng Cao; Rui Zhou; Rui Wu (Ocean Engineering, 2026)

Cosmic spike removal based on multi-feature fusion for long-time integrated Raman spectral detection - Huijie Wang; Xu Liu; Xujin Hu; Wenhui Sun; Shuang Xiong; Jinjin Wu; Linwei Shang; Jianhua Yin (Analytica Chimica Acta, 2026)

Experimental investigation of bubble morphology and instantaneous impact characteristics in submerged jets - Yongfei Yang; Wenxiao Wang; Weidong Shi; Xianglong Wu; Linwei Tan; Yupeng Cao; Yu Lu; Chunhui Ma (Ocean Engineering, 2026)

Failure pattern of ring-shaped leakage-induced ground collapse under varying pipeline fracture spacings in red clay areas: Insights from semiphysical modeling - Kai Wang; Linwei Li; Xiqiong Xiang; Yiping Wu; Fasheng Miao (Engineering Geology, 2026)

Warming increases viral diversity and the relative abundance of virulent viruses in deep soils - Yiqing Lv; Xiaomin Fan; Xiangyu Fan; Wenkuan Qin; Xudong Wang; Xin Sun; Biao Zhu; Linwei Wu (Soil Biology and Biochemistry, 2026)

Virus-inclusive microbial network relationships align with the stress gradient hypothesis in saline-alkali agroecosystems - Fang Li; Linwei Wu; Changlin Xu; Shuwen Guo; Jinhua Zhao; Yi Wang; Peipei Li; Biao Zhu (Soil Biology and Biochemistry, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Metagenomic insights into the global distribution and functional potentials of major polyphosphate-accumulating organisms (PAOs) in activated sludge wastewater treatment plants - Zhenhui Yang; Yi Yang; Daliang Ning; Xiaomin Fan; Yiqing Lv; Linlan Zhuang; Linwei Wu (Water Research, 2026)

Preparation of specific and sensitive monoclonal antibodies for thiamethoxam and development of immunoassay methods for detecting thiamethoxam in lake water, vegetables, and animal-derived foods - Jiacan Wang; Yiting Wang; Shixiang Wu; Linwei Zhang; Hao Wen; Hongfei Yang; Xu Wang; Dapeng Peng (Food Bioscience, 2026)

Isolation and characterization of a novel reassortant H3N8 avian influenza virus from chickens in Eastern China - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Taoming Tang; Zhigang Wu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Amino acid substitutions associated with adaptation of novel H10N3 and H10N5 avian influenza viruses to mice - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2025)

Formaldehyde emissions in tanker truck cabins: Observation, deep learning prediction and health risk assessment - Rui Zhang; Dongdong Guo; Ruixiu Jiang; Honglin Cao; Yunjia Wu; Lirong Kou; Meng Wang; Linwei Xi; Yang Liu; Haimei Wang; Jianyin Xiong (Science of The Total Environment, 2025)

Biodegradable polylactic acid (PLA) copolymer materials: Structural design, synthesis strategy, the relationship between structure and performance, industrial application - Rongrong Ji; Fan Mo; Linwei Liang; Chen Tian; Shixing Dong; Chang Deng; Hao Wu; Ling Zhou; Xipo Zhao (Chemical Engineering Journal, 2025)

Localized surface plasmon enhancement strategy with synergistic dual-mechanism fluorescence quenching for developing highly sensitive lateral flow immunoassays - Mingyue Ding; Hao Wen; Long Li; Yu Si; Jixiang Liang; Shixiang Wu; Linwei Zhang; Hongfei Yang; Shiyun Han; Xiaoming Pan; Yiting Wang; Jiacan Wang; et al. (Chemical Engineering Journal, 2025)

Multiple surge trigger mechanisms of compound glacier: a case study on recent surges of Aru-4 Glacier, Western Tibetan Plateau - Weijin Guan; Bo Cao; Linwei Sha; Baotian Pan; Xuanru Zhao; Zongli Jiang; Guangjian Wu (Journal of Mountain Science, 2025)
Surge-type glaciers are widely developed in mountainous areas around the world. Understanding the trigger mechanism of glacier surge is a prerequisite for addressing their impacts on hydrological assessments, disentangling climate-glacier linkages, and mitigating downstream hazards. Most glacier surges occur in the compound glaciers; however, attention paid to the trigger mechanisms of such surges is minimal. This study confirmed two surges in the northern and southern branches of the Aru-4 glacier, respectively, in the Western Tibetan Plateau, using multisource remote sensing data. The northern branch of the Aru-4 glacier entered the active phase in 1999 and the active phase lasted for 6 years. The southern branch of the Aru-4 glacier entered the active phase in 2007 and the active phase lasted for 9 years. The southern branch of the Aru-4 glacier experienced a long period of retreat before the northern branch surged and their tongues were in a detached state. The northern branch surge carried a large amount of ice to the frontal area, blocking the downward transport of ice from the southern branch and initiated surge. Through the analysis of two surge processes of Aru-4 glacier, we found a new surge mechanism for compound glaciers. It was revealed that surges in such glaciers are not only triggered by the reduction in basal sliding resistance caused by the internal factors. These surges initiated in the upper part of the glacier then propagated to down glacier by intense compression force. Furthermore, surges can also be triggered by external intervention of blocking by other branches. This external trigger initiates the surge in the lower part of the glacier then propagated to the upper part by longitudinal traction force. In addition, comparing with the surge triggered by the internal factors, the surge triggered by the external intervention may have a more dramatic process.

Identification of the exposure pathway to micro-scaled biogenic silica debris via diet and its potential effect in promoting esophageal squamous cell carcinoma - Shenxi Deng; Yi Yang; Erica Celeste Conway; Si Li; Cha Huang; Zigu Chen; Haisheng Wu; Yuan He; Shuzhe Xie; Aifang Ji; Jingyan Zhang; Yansheng Gu; et al. (Journal of Hazardous Materials, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

Observational climatology and interannual variability of the spring rainy season onset over southern China: Objective definition and influence from tropical Pacific Ocean - Kexu Zhu; Wen Chen; Peng Hu; Yehong Luo; Ruowen Yang; Linwei Jiang; Qingyu Cai; Lu Gao; Jingnan Li; Yongmao Peng; Changhao Wu; Ziqi Niu (Atmospheric Research, 2025)

Combined multispectral analysis and molecular docking to research the interaction of soybean isolate protein with different kinds of phospholipid liposomes and its effect on liposome properties - Linwei Zhao; Chunlei Liu; Tong Wang; Libin Sun; Fei Wu; Dianyu Yu (Food Chemistry, 2025)

Probabilistic Assessment of Constitutive Model Parameters: Insight from a Statistical Damage Constitutive Model and a Simple Critical State Hypoplastic Model - Yang Xue; Fasheng Miao; Yiping Wu; Linwei Li; Daniel Dias; Yang Tang (Journal of Earth Science, 2025)

Electroformation and characterization of soybean protein isolate hydrolysates-modified liposomes - Libin Sun; Linwei Zhao; Zhe Huang; Fei Wu; Mingzhe Pan; Dianyu Yu (Food Hydrocolloids, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Probabilistic back analysis of reservoir landslide considering hydro-mechanical coupled observations - Yang Xue; Fasheng Miao; Jingze Li; Yiping Wu; Linwei Li (Computers and Geotechnics, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Using Multi-Source data to identify high NOx emitting Heavy-Duty diesel vehicles - Zhuoqian Yang; Ke Han; Linwei Liao; Jiaxin Wu (Transportation Research Part D: Transport and Environment, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Development of time-resolved fluorescence immunochromatography and ic-ELISA based on monoclonal antibodies specifically recognizing fumonisin B1 - Xiaoming Pan; Yalin Yang; Huaming Li; Jiaxu Xiao; Linwei Zhang; Shixiang Wu; Hao Wen; Bencheng Wu; Dapeng Peng (Food Bioscience, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Macro and micro connections for slip zone soils of landslide under wetting–drying cycles in the Three Gorges Reservoir area - Fasheng Miao; Fancheng Zhao; Yiping Wu; Linwei Li; Yanming Ding; Jiajia Meng (Landslides, 2024)

Effects of hypobaria, hyperoxia, and nitrogen form on the growth and nutritional quality of lettuce - Linwei Jia; Yongkang Tang; Ke Tian; Weidang Ai; Wenjin Shang; Hao Wu (Life Sciences in Space Research, 2024)

Effects of acid mine drainage on photochemical and biological degradation of dissolved organic matter in karst river water - Linwei Li; Xingxing Cao; Chujie Bu; Pan Wu; Biao Tian; Yongheng Dai; Yeye Ren (Journal of Environmental Sciences, 2024)

Structural effects of sulfonamides on the proliferation dynamics of sulfonamide resistance genes in the sequencing batch reactors and the mechanism - Ligui Wu; Mingyu Wang; Lingling Rong; Wenbiao Wang; Linwei Chen; Qiaofeng Wu; Haoyu Sun; Xiangfeng Huang; Xiaoming Zou (Journal of Environmental Sciences, 2024)

Automatic identification of illegal construction and demolition waste landfills: A computer vision approach - Qiaoqiao Yong; Huanyu Wu; Jiayuan Wang; Run Chen; Bo Yu; Jian Zuo; Linwei Du (Waste Management, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Spatio-temporal characterization of dissolved organic matter in karst rivers disturbed by acid mine drainage and its correlation with metal ions - Linwei Li; Xingxing Cao; Pan Wu; Chujie Bu; Yeye Ren; Kai Li (Science of The Total Environment, 2023)

Landslide susceptibility mapping in Three Gorges Reservoir area based on GIS and boosting decision tree model - Fasheng Miao; Fancheng Zhao; Yiping Wu; Linwei Li; Ákos Török (Stochastic Environmental Research and Risk Assessment, 2023)

Fluoxetine alleviates postoperative cognitive dysfunction by attenuating TLR4/MyD88/NF-κB signaling pathway activation in aged mice - Yusheng Yao; Daoyi Lin; Yuzhi Chen; Linwei Liu; Yushang Wu; Xiaochun Zheng (Inflammation Research, 2023)

Combing soil spatial variation and weakening of the groundwater fluctuation zone for the probabilistic stability analysis of a riverside landslide in the Three Gorges Reservoir area - Yang Xue; Fasheng Miao; Yiping Wu; Daniel Dias; Linwei Li (Landslides, 2023)

Slope Instability Analysis of the Qiongdongnan Basin in the Northern Part of the South China Sea: Implications for the Risk Evaluation of Deepwater Drilling - Linwei Ma; Shiguo Wu; Yanrui Liu; Jin Sun; Min Ouyang; Qingping Li; Yongpeng Qin; Dawei Wang (Journal of Ocean University of China, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Adaptive hybrid machine learning model for forecasting the step-like displacement of reservoir colluvial landslides: a case study in the three Gorges reservoir area, China - Li Linwei; Wu Yiping; Huang Yepiao; Li Bo; Miao Fasheng; Deng Ziqiang (Stochastic Environmental Research and Risk Assessment, 2023)

Experimental insights into the formation of secondary minerals in acid mine drainage-polluted karst rivers and their effects on element migration - Yeye Ren; Xingxing Cao; Pan Wu; Linwei Li (Science of The Total Environment, 2023)

Optimized Apriori algorithm for deformation response analysis of landslide hazards - Li Linwei; Wu Yiping; Huang Yepiao; Li Bo; Miao Fasheng; Deng Ziqiang (Computers & Geosciences, 2023)

Permafrost thaw with warming reduces microbial metabolic capacities in subsurface soils - Linwei Wu; Felix Yang; Jiajie Feng; Xuanyu Tao; Qi Qi; Cong Wang; Edward A. G. Schuur; Rosvel Bracho; Yi Huang; James R. Cole; James M. Tiedje; Jizhong Zhou (Molecular Ecology, 2022)
Microorganisms are major constituents of the total biomass in permafrost regions, whose underlain soils are frozen for at least two consecutive years. To understand potential microbial responses to climate change, here we examined microbial community compositions and functional capacities across four soil depths in an Alaska tundra site. We showed that a 5‐year warming treatment increased soil thaw depth by 25.7% ( p = .011) within the deep organic layer (15–25 cm). Concurrently, warming reduced 37% of bacterial abundance and 64% of fungal abundances in the deep organic layer, while it did not affect microbial abundance in other soil layers (i.e., 0–5, 5–15, and 45–55 cm). Warming treatment altered fungal community composition and microbial functional structure ( p p

A hybrid interval displacement forecasting model for reservoir colluvial landslides with step-like deformation characteristics considering dynamic switching of deformation states - Linwei Li; Yiping Wu; Fasheng Miao; Yang Xue; Yepiao Huang (Stochastic Environmental Research and Risk Assessment, 2021)

Effect of weakening of sliding zone soils in hydro-fluctuation belt on long-term reliability of reservoir landslides - Kang Liao; Yiping Wu; Fasheng Miao; Linwei Li; Yang Xue (Bulletin of Engineering Geology and the Environment, 2021)

Triggering factors and threshold analysis of baishuihe landslide based on the data mining methods - Fasheng Miao; Yiping Wu; Linwei Li; Kang Liao; Yang Xue (Natural Hazards, 2021)

Time-varying reliability analysis of Majiagou landslide based on weakening of hydro-fluctuation belt under wetting-drying cycles - Kang Liao; Yiping Wu; Fasheng Miao; Linwei Li; Yang Xue (Landslides, 2021)

Using a kernel extreme learning machine with grey wolf optimization to predict the displacement of step-like landslide - Kang Liao; Yiping Wu; Fasheng Miao; Linwei Li; Yang Xue (Bulletin of Engineering Geology and the Environment, 2020)

Effect of spatially variable saturated hydraulic conductivity with non-stationary characteristics on the stability of reservoir landslides - Yang Xue; Yiping Wu; Fasheng Miao; Linwei Li; Kang Liao; Guangzhao Ou (Stochastic Environmental Research and Risk Assessment, 2020)

Study of the Sensitive Properties of Marine Gas Hydrate Based on the Prestack Elastic Inversion - Siyou Tong; Jialin Wang; Linwei Li; Haiqi Zhang; Zhiqiang Wu; Yulan Shao (Journal of Ocean University of China, 2019)

Reverse-Time Migration of Converted S-Waves of Varying Densities - Siyou Tong; Ming Chen; Huawei Zhou; Linwei Li; Xiugang Xu; Zhiqiang Wu (Journal of Ocean University of China, 2019)

The spatial scale dependence of diazotrophic and bacterial community assembly in paddy soil - Qun Gao; Yunfeng Yang; Jiajie Feng; Renmao Tian; Xue Guo; Daliang Ning; Lauren Hale; Mengmeng Wang; Jingmin Cheng; Linwei Wu; Mengxin Zhao; Jianshu Zhao; et al. (Global Ecology and Biogeography, 2019)
Aim The factors driving microbial community β‐diversity (variation in composition) at different spatial scales yield fundamental insights into the mechanisms that maintain ecosystem biodiversity, which as yet are uncertain. Here, we explore whether spatial scale‐dependent patterns of β‐diversity vary between microbial functional groups and bacterial taxa (i.e., diazotrophic and bacterial communities) across local to regional scales (from metres to hundreds of kilometres). Location Eastern China. Time period October and November 2015. Major taxa studied Diazotrophic and bacterial communities. Methods We use two complementary statistical tools to unveil biotic mechanisms (i.e., species association) underlying variation in β‐diversity of diazotrophic and bacterial communities. We examined distance–decay slopes of both communities at the local (1–113 m), meso‐ (3.4–39 km) and regional (103–668 km) scales. We used an environmentally constrained checkerboard score and topological features of association networks as indices of species association. We then calculated contributions of species association, abiotic factors and geographical distance to explain community β‐diversity. The scale‐dependent distance–decay relationships were also examined in ubiquitous (high occupancy across samples) and endemic communities of diazotrophs and bacteria. Results Diazotrophs displayed steeper distance–decay slopes than bacteria, suggesting that the β‐diversity of diazotrophic communities was more variable. The distance–decay slopes were dependent on spatial scales in both communities, owing to different contributions of geographical distance, abiotic factors and species association at three spatial scales. Intriguingly, species association was greater and contributed more to community β‐diversity than other forces at the local scale, implying that species association could greatly alter community structures. Main conclusions Drivers of diazotrophic and bacterial community β‐diversity depended on spatial scales, resulting in different distance–decay patterns. Moreover, this was the first study to use two methods to demonstrate that species association played important, but as yet unrecognized, roles in driving spatial scale‐dependent β‐diversity.

Risk assessment of snowmelt-induced landslides based on GIS and an effective snowmelt model - Fasheng Miao; Yiping Wu; Linwei Li; Kang Liao; Longfei Zhang (Natural Hazards, 2019)

Dissimilar responses of fungal and bacterial communities to soil transplantation simulating abrupt climate changes - Mengxin Zhao; Bo Sun; Linwei Wu; Feng Wang; Chongqing Wen; Mengmeng Wang; Yuting Liang; Lauren Hale; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2019)
Both fungi and bacteria play essential roles in regulating soil carbon cycling. To predict future carbon stability, it is imperative to understand their responses to environmental changes, which is subject to large uncertainty. As current global warming is causing range shifts toward higher latitudes, we conducted three reciprocal soil transplantation experiments over large transects in 2005 to simulate abrupt climate changes. Six years after soil transplantation, fungal biomass of transplanted soils showed a general pattern of changes from donor sites to destination, which were more obvious in bare fallow soils than in maize cropped soils. Strikingly, fungal community compositions were clustered by sites, demonstrating that fungi of transplanted soils acclimatized to the destination environment. Several fungal taxa displayed sharp changes in relative abundance, including Podospora , Chaetomium , Mortierella and Phialemonium . In contrast, bacterial communities remained largely unchanged. Consistent with the important role of fungi in affecting soil carbon cycling, 8.1%–10.0% of fungal genes encoding carbon‐decomposing enzymes were significantly ( p

Evaluating the lingering effect of livestock grazing on functional potentials of microbial communities in Tibetan grassland soils - Mengmeng Wang; Shiping Wang; Linwei Wu; Depeng Xu; Qiaoyan Lin; Yigang Hu; Xiangzhen Li; Jizhong Zhou; Yunfeng Yang (Plant and Soil, 2016)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.